Refugee economies in Dollo Ado: development opportunities in a border region of Ethiopia - Betts, A; Bradenbrink, R; Greenland, J; Omata, N; Sterck, O (Refugee Studies Centre, 2019)
This report examines the economic strategies of Somali refugees in the cross-border economy of Ethiopia’s Somali region. The five Dollo Ado refugee camps were created between 2009 and 2011 in the Somali Region of Ethiopia. According to UNHCR registration data, they host around 220,000 almost exclusively Somali refugees within a semi-arid and isolated border district within which refugees outnumber the host population. The camps and host community have benefited significantly from the IKEA Foundation’s €75m investment in the camps over a seven-year period. This globally unprecedented level of private sector investment has created a range of new opportunities in education, entrepreneurship, energy, agriculture, the environment, and livelihoods.